PENGEMBANGAN BUKU SAKU WISATA KULINER EKONOMI KREATIF DI MUARA BUNGO - INDARSIH, FITRIA RETNO (Jurnal Pendidikan Vokasi dan Seni, 2023)
The development of the tourism sector has been established by Creative Economic Agency (BEKRAF) as one of the creative cities in the field of culinary, fashion, and crafts. But not many people know about the existence of some reference books and the absence of a guidebook about creative economy culinary tourism affect the tourists’ interest in creative economy culinary tourism in Muara Bungo. This thing became the purpose of the study is to discuss some problems that intended to be disclosed are: 1) To develop a creative economy culinary tour pocketbook; 2) To analyze the feasibility of a creative economy culinary tour pocketbook; 3) To analyze the practicality of a creative economy culinary tour pocket book to tourists, and 4) To analyze the effectiveness of a creative economy culinary tour pocket book to interest tourists. This research used the R&D method (Research and Development) which refers to the model development of ADDIE (Analysis, Design, Development, Implementation, Evaluation). Population and Sample are obtained from all travelers who travel to Semarang city. Based on assessment results, it can be found that the validator expert obtained an average score of 4,58 included in the category of very decent, and material experts got an average score of 4,72 included in the category of very decent, assessment result done by the respondents that are focused on the practicality of a pocket book is in the category of overall positive position with an average score of 97,5%, and the questionnaire results of tourists’ interests to the creative economy culinary tour pocket book categorized as an effective thing because it reaches 4,26%. This shows that the creative economy culinary tour pocketbook can affect the tourists’ interests.